Hybridizing δ-Type MnO2 With Lignin-Derived Porous Carbon as a Stable Cathode Material for Aqueous Zn–MnO2 Batteries - Zhou, Weijun; Wang, Anran; Huang, Aixiang; Chen, Minfeng; Tian, Qinghua; Chen, Jizhang; Xu, Xinwu (Frontiers in Energy Research, 2020)
With the advantages of intrinsic safety, low price, high output potential, and acceptable energy density, aqueous rechargeable Zn–MnO2 batteries are gradually emerging as promising energy storage devices in recent years. Unfortunately, the structural instability and poor electrical conductivity of manganese dioxides still hinder their further applications. To tackle these issues, we demonstrate a high-performance cathode material for Zn–MnO2 batteries by hybridizing lignin-derived porous carbon with δ-MnO2 (denoted as LPC/δ-MnO2). Benefiting from the high electrical conductivity of porous carbon, the LPC/δ-MnO2 cathode material can offer high discharge capacity of 332.3 mAh g–1 at 0.2 A g–1 and excellent high-rate capability (196.1 mAh g–1 at 5 A g–1). Meanwhile, the assembled Zn–MnO2 battery displays good long-term cycling stability (82% capacity retention after 1000 cycles). Such superior performances are attributed to the synergetic effect of nanostructured δ-MnO2 and porous carbon scaffold, which is in favor of rapid Zn2+ ion diffusion and large contribution ratio of pseudocapacitive Zn2+ ion intercalation. The results of this study show great prospects of hybridizing biomass-derived carbon framework with electrochemically active materials toward advanced energy storage materials.